(untitled) (Research, Society and Development, 2021)
This study investigated the training of undergraduate students in Biological Sciences related to the cross-cutting theme of the environment, an experience experienced during the development of the discipline Teaching Practice V in the Faculty of Science and Technology Professor Dirson Maciel de Barros. The objective was to analyze the formative contributions for the biology undergraduate students of the teaching experience in Basic Education with the teaching of Environmental Education. The course emphasized the programmatic content related to Cross-Cutting Themes, which were developed in the form of extension projects in public schools in the municipality of Goiana-PE, thus promoting the partnership between University and School as a way to provide undergraduates the initial opportunity to interact with their future field of professional activity. The research, qualitative in nature, was characterized in its ends as descriptive and in its means as a field study. From the experiences in the classroom, the students made projects with the theme of Environmental Education and applied them in state public schools in the city of Goiana-PE. As a result, the projects developed by the students in the schools contained methodological and didactic teaching proposals that can later be developed by teachers. It can be concluded that, during the teaching experience, the teacher constructs his or her knowledge based on the relationship with the students and the school reality. In addition, they were able to contribute to the teaching-learning process of the basic education students and, mainly, to their own learning.